Pretreatment and enzymatic hydrolysis of lignocellulosic biomass - Corredor, Deisy Y. (Kansas State University, 2008)
The performance of soybean hulls and forage sorghum as feed stocks for ethanol production was studied. The main goal of this research was to increase fermentable sugars' yield through high-efficiency pretreatment technology. Soybean hulls are a potential feedstock for production of bio-ethanol due to their high carbohydrate content ([approximately equals]50%) of nearly 37% cellulose. Soybean hulls could be the ideal feedstock for fuel ethanol production, because they are abundant and require no special harvesting and additional transportation costs as they are already in the plant. Dilute acid and modified steam-explosion were used as pretreatment technologies to increase fermentable sugars yields. Effects of reaction time, temperature, acid concentration and type of acid on hydrolysis of hemicellulose in soybean hulls and total sugar yields were studied. Optimum pretreatment parameters and enzymatic hydrolysis conditions for converting soybean hulls into fermentable sugars were identified. The combination of acid (H[subscript]2SO[subscript]4, 2% w/v) and steam (140 °C, 30 min) efficiently solubilized the hemicellulose, giving a pentose yield of 96%. Sorghum is a tropical grass grown primarily in semiarid and dry parts of the world, especially in areas too dry for corn. The production of sorghum results in about 30 million tons of byproducts mainly composed of cellulose, hemicellulose, and lignin. Forage sorghum such as brown midrib (BMR) sorghum for ethanol production has generated much interest since this trait is characterized genetically by lower lignin concentrations in the plant compared with conventional types. Three varieties of forage sorghum and one variety of regular sorghum were characterized and evaluated as feedstock for fermentable sugar production. Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) and X-Ray diffraction were used to determine changes in structure and chemical composition of forage sorghum before and after pretreatment and enzymatic hydrolysis process. Up to 72% of hexose yield and 94% of pentose yield were obtained using "modified" steam explosion with 2% sulfuric acid at 140°C for 30 min and enzymatic hydrolysis with cellulase (15 FPU/g cellulose) and [Beta]-glucosidase (50 CBU/g cellulose).
Keywords: Ethanol; Hydrolysis; Pretreatment; Forage; Engineering, Agricultural (0539); Engineering, Chemical (0542)